Forecasting stock market returns by summing the frequency-decomposed parts - Gonçalo Faria; Fabio Verona (Bank of Finland, 2016)
We generalize the Ferreira and Santa-Clara (2011) sum-of-the-parts method for forecasting stock market returns. Rather than summing the parts of stock returns, we suggest summing some of the frequency-decomposed parts. The proposed method signi cantly improves upon the original sum-of-the-parts and delivers statistically and economically gains over historical mean forecasts, with monthly out-of-sample R2 of 2.60% and annual utility gains of 558 basis points. The strong performance of this method comes from its ability to isolate the frequencies of the parts with the highest predictive power, and from the fact that the selected frequency-decomposed parts carry complementary information that captures di erent frequencies of stock market returns.
URN:NBN:fi:bof-201611301505
Keywords: G11; G12; G14; G17; 330